Visual representation of domestic violence in Kompas.com and Detik.com - Muria Endah Sokowati; Fauziah Hassan (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2024)
Domestic violence cases are increasingly being exposed in various news outlets, reporting women are disproportionately affected by both physical and sexual violence. The extensive coverage of these incidents represents a significant advancement in empowering women's positions. Nevertheless, given the enduring influence of patriarchal society within the media business, it is necessary to do a more in-depth analysis of how women are depicted while reporting domestic violence, especially from visual representations. The author investigated the news reporting of domestic violence from Kompas.com and Detik.com during 2022-2023. The analysis revealed that there is ambiguity in representing women as the victims of domestic violence. The two outlets' progressive approach is evident in the narrative, as they position the women as the subjects. However, from the visual images, both outlets continue to perpetuate the notion of women as victims by portraying them in a prejudiced manner.